My future-self has (not) quit smoking: An experimental study into the effect of a future-self intervention on smoking-related self-identity constructs. (March 2023) - Penfornis, Kristell M.; Gebhardt, Winifred A.; Rippe, Ralph C.A.; Van Laar, Colette; van den Putte, Bas; Meijer, Eline
Abstract: Objectives: Envisioning one's (non)smoking future may make (un)desired future identities more accessible, salient, and personally relevant and facilitate smoking cessation. The current study assessed whether a future-self intervention can weaken smoker self-identity and expected identity loss when quitting smoking, and strengthen quitter- and nonsmoker self-identity, while accounting for personal factors—socioeconomic position, nicotine dependence, consideration of future consequences, and clarity of the envisioned future-self. Additionally, it examined the association between smoking-related identity and quitting intention and behavior. Methods: This longitudinal online experimental study randomized 233 adult smokers to an intervention condition (where they completed mental imagery, visual, and verbal tasks about a future (non)smoking self), or to a passive control condition. Smoker-, quitter-, nonsmoker self-identity and identity loss were measured post-intervention and after one- and three-months. Quit intention and attempts were measured at baseline and after one month. Results: There was a consistent increase in non-smoker self-identity, and decrease in smoker self-identity and identity loss over a period of six months for all participants, but no significant difference in smoking-related identity between the intervention and control group. While personal factors did not moderate the effect of the intervention, we found that smoking-related identity constructs do vary with nicotine dependence, consideration of future consequences, and clarity of the envisioned future-self. Quitting behavior is primarily associated with non-smoker self-identity. Conclusions: Although the future-self intervention did not significantly influence smoking-related identity or behavior, identity—in particular, non-smoker self-identity—is important to consider in smoking cessation interventions. More research is needed to find effective operationalizations for identity-based interventions in the context of smoking. Highlights: Examined the effect of a future-self intervention on smoking-related identity. The intervention was unsuccessful in influencing identity and needs improvement. Multilevel analyses showed a natural fluctuation of identity over time. Self-identity plays an important role in smoking cessation intention and attempts. Psychosocial factors are significantly associated with smoking-related identity.